2017
DOI: 10.1021/acsbiomaterials.6b00762
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin-Loaded Photosensitizer-Core pH-Responsive Copolymer Nanocarriers for Combining Photodynamic Therapy and Chemotherapy

Abstract: Photodynamic therapy (PDT) is an emerging method for the treatment of cancer. Combination of PDT and chemotherapy is a hot topic though the two therapies could not simultaneously exert their perfect effect in vivo. Here we report a doxorubicin-loaded photosensitizer-core pH-responsive copolymer nanocarrier with high tumor targeting and anticancer effects due to integration of PDT with chemotherapy. The pH-responsive photosensitizer-core four-armed star-shaped copolymer, [methoxy-poly(ethylene glycol)poly(2-(N,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 33 publications
2
36
0
Order By: Relevance
“…DOX was also used as the chemotherapeutic agent in four-armed star-shaped copolymer based on ZnPc as the PS ( Scheme 12 ). The copolymer presented a tendency to self-assemble into DOX-loaded micelles [ 78 ], which had high tumor targeting and anticancer effects thanks to a combination of the two therapies. The pH-responsive photosensitizer-core four-armed star-shaped copolymer, [methoxy-poly(ethylene glycol)-poly(2-(N,N-diethylamino)ethyl methacrylate)-poly(ε-caprolactone)]4-zinc β-tetra-(4-carboxyl benzyloxyl)phthalocyanine (PDCZP) was successfully designed and prepared.…”
Section: Phthalocyanine-polymeric Nanoparticle Delivery Systems For Cancer Photodynamic Therapymentioning
confidence: 99%
“…DOX was also used as the chemotherapeutic agent in four-armed star-shaped copolymer based on ZnPc as the PS ( Scheme 12 ). The copolymer presented a tendency to self-assemble into DOX-loaded micelles [ 78 ], which had high tumor targeting and anticancer effects thanks to a combination of the two therapies. The pH-responsive photosensitizer-core four-armed star-shaped copolymer, [methoxy-poly(ethylene glycol)-poly(2-(N,N-diethylamino)ethyl methacrylate)-poly(ε-caprolactone)]4-zinc β-tetra-(4-carboxyl benzyloxyl)phthalocyanine (PDCZP) was successfully designed and prepared.…”
Section: Phthalocyanine-polymeric Nanoparticle Delivery Systems For Cancer Photodynamic Therapymentioning
confidence: 99%
“… Molecular structure of PDCZP and illustration of its pH-dependent drug release and combination of chemotherapy and photodynamic therapy. Reproduced from [ 169 ] with permission, copyright 2017, American Chemical Society. …”
Section: Figures Schemes and Tablesmentioning
confidence: 99%
“…The DOX-loaded nanovehicles showed the formation of 50 nm-sized spherical particles at pH 7.4. In the nanovehicles delivered to tumor cells, the rapid DOX release was triggered by the acidic pH, resulting in enhanced antitumor effects through chemotherapy with DOX and PDT with core PS under light irradiation (Figure 10) [169]. [169] with permission, copyright 2017, American Chemical Society.…”
Section: De/protonation Triggered By Light-and Ph-dual-responsive Nanovehiclesmentioning
confidence: 99%
See 1 more Smart Citation
“…For dual delivery systems, Zhang et al [ 166 ] reported the high tumor-targeting and anticancer effects of Dox-loaded photosensitizer-core pH-responsive copolymer nanocarrier prepared from a four-armed star-shaped copolymer, [methoxy-poly(ethylene glycol)-poly(2-( N , N -diethylamino)ethyl methacrylate)-poly(ε-caprolactone)] 4 -zinc β-tetra-(4-carboxyl benzyloxyl)phthalocyanine (PDCZP). The nanocarriers loaded with zinc phthalocyanine (ZnPc) had a long emission wavelength (max.…”
Section: Polymer-based Photosensitive Nanomedicinementioning
confidence: 99%